Ethical prompting: toward strategies for rapid and inclusive assistance in dual-use AI systems - Farnós, Joan; Sans Pinillos, Alger; Costa, Vicent (Frontiers in Artificial Intelligence, 2025)
Monitoring technologies initially developed for individuals with disabilities carry inherent dual-use risks, especially evident in conflict or emergency scenarios. This article examines the dual-use dilemma posed by technologies whose civilian design objectives can unintentionally facilitate harmful applications in defense contexts. Specifically, we analyze the ethical risks associated with using civilian-generated data and systems, originally intended to enhance care and assistance, for military purposes without adequate safeguards. We argue that effective and ethically sound technological infrastructures require optimized and ethically-informed prompting strategies. These strategies must clearly define how data and system prompts are structured, reducing deployment biases, particularly against vulnerable populations.